Frequency of Microalbuminuria in Essential Hypertension and type II Diabetes Mellitus in Tertiary Care Hospital - Somia Tariq, Irfan Raheem, Ishtiaque Ahmed Mahar, Samiya Rehman (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Hypertension is the growing issues of public health problem of adult population in both developed as well as developing world, affecting single person in every four people. Objectives: The main objective of the study is to find the frequency of microalbuminuria in essential hypertension in tertiary care hospitals. Material and Methods: This Randomized Control Trial was conducted in DHQ hospital Sahiwal during 2020 to 2021. Blood sample of all the patients diagnosed with microalbuminuria in hypertension presented to the hospital were taken and sent to laboratory for performing fasting blood glucose and 1st morning Urine sample was taken and analyzed for albumin to creatinine ratio of these patients. Results: The age range of patients in this research was from 18-75 years. The mean age of patients was 40.35 ± 8.65 years. In group A the mean age of patients was 39.60 ± 10.12 years and in group B was 41.0 ± 8.05 years. Conclusion: This study concluded that efficacy of losartan is higher than lisinopril for reduction of microalbuminuria in patients with type-2 diabetes mellitus. Keywords: type II diabetes, microalbuminuria, losartan